ATG7 vs. ATG5: Distinct autophagy pathways shaping TGF-β signaling and endothelial function - Aman Singh; Bharatsinai Peddi; Kriti S. Bhatt; Hien C. Nguyen; Krishna K. Singh (PLoS ONE, 2026)
Autophagy and transforming growth factor-beta (TGF-β) signaling are critical cellular processes that maintain homeostasis and regulate various physiological functions, including endothelial cell function. This study explores the distinct roles of two essential autophagy regulators, autophagy-related gene 5 (ATG5) and ATG7, in modulating TGF-β signaling and endothelial function. To this end, ATG5 and ATG7 were selectively silenced in endothelial cells, with knockdown efficiency confirmed via RT-qPCR and Western blot analyses. Gene expression profiling revealed differential regulation of TGF-β signaling components following ATG5 or ATG7 silencing. Functional assays demonstrated that ATG5 knockdown enhanced endothelial cell proliferation and migration, whereas ATG7 silencing produced distinct, less pronounced effects. Furthermore, downstream effectors of the TGF-β pathway exhibited gene-specific modulation, underscoring divergent roles of ATG5 and ATG7 in this signaling cascade. Collectively, these findings highlight the non-redundant functions of ATG5 and ATG7 in coordinating TGF-β signaling pathways, offering new insights into their contribution to endothelial physiology and potential as therapeutic targets in vascular pathologies.